Tissue engineering scaffold for sequential release of vancomycin and rhBMP2 to treat bone infections. Issue 12 (5th February 2014) - Pacheco, Hernando; Vedantham, Kumar; Aniket; Young, Amy; Marriott, Ian; El‐Ghannam, Ahmed
Abstract The ability of silica calcium phosphate nanocomposite (SCPC75) for the controlled sequential delivery of vancomycin (Vanc) and rhBMP2 was evaluated. Fourier transform infrared spectroscopy analyses of the SCPC75 showed an increase in the bond energy of the PO4−3 due to the interactions with negatively charged moieties of Vanc. Furthermore, a decrease in the bond energy of the SiOSi functional groups was observed after rhBMP2 adsorption. In conjunction with the differences in bond site and bond energy at the ceramic/drug interface, significant differences in drug release kinetics and bioceramic dissolution rate were found. UV–vis spectrometry showed a burst release of Vanc in the first 8 h followed by a sustained release stage for up to 28 days. ELISA showed first‐order release kinetics of rhBMP2 without burst release. The rhBMP2 release from SCPC75 was associated with a significantly lower rate of Ca and a higher rate of Si dissolutions when compared with Vanc release over identical time periods. Differences in the release kinetic profiles of Vanc and rhBMP2 from the SCPC75‐Vanc/SCPC75‐rhBMP2 scaffolds at 70/30, 50/50, or 20/80 ratios allowed for sequential drug release profiles that could be exploited to customize doses and release duration of each drug. The released rhBMP2 significantly upregulated MC3T3‐E1 expression of collagen type I, osteopontin, and osteocalcin mRNA by 12.6‐, 3.3‐, and 2.4‐fold, respectively. The released Vanc demonstrated bactericidal effects on Staphylococcus aureus in vitro. These results suggest the potential of SCPC75‐Vanc‐rhBMP2 scaffolds in the treatment of damaged and/or infected bone. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 4213–4223, 2014.